When do older birds better resist stress? A study of the corticosterone stress response in snow petrels - Angelier, Frédéric (Biol Lett, 2020)
Life-history theory predicts that, to optimize their fitness, individuals should increase their reproductive effort as their residual reproductive value decreases. Accordingly, several studies have shown that individuals downregulate their glucocorticoid stress response (a proxy of reproductive investment in vertebrates) as they age, and as the subsequent reproductive value decreases. However, and surprisingly, results appear inconsistent, suggesting that the environmental context or the individual state may affect the relationship between age and reproductive effort. Here, we tested for the first time this hypothesis, and more specifically, whether this attenuation of the corticosterone stress response with advancing age depends on the energetic status of individuals. We compared the influence of age on the corticosterone stress response between fasting and non-fasting breeding snow petrels (Pagodroma nivea), an extremely long-lived bird. As expected, we found that the corticosterone stress response was attenuated in old petrels, but only when they were not fasting. Interestingly, this pattern was not apparent in fasting petrels, suggesting that old birds downregulate their corticosterone stress response and increase their parental investment only when they are in good body condition. At the ultimate level, old individuals may maintain a strong corticosterone stress response when fasting because the survival costs of increased stress resistance and parental effort might then outweigh their reproductive benefits.